Pengaruh Konsetrasi Carboxymethylcellulose (CMC) dan Gula Stevia terhadap Karakter Sirup Buah Tin (Ficus carica, L) - Widyastuti, Retno; Afriyanti, Afriyanti; Asmoro, Novian Wely; Hartati, Sri (Program Studi Teknologi Pangan, 2018)
Processing figs into food and beverage products will increase the attractiveness to consume this nutrient-rich fruit. One of them is by processing it into syrup. The purpose of this study is to (1) Knowing the effect of the stevia sugar concentration on the physical and chemical characteristics of fig syrup; (2) Knowing the effect of the carboxymethylcellulose (CMC) concentration on the physical and chemical characteristics of fig syrup. The experimental design used in this study was a completely randomized design (CRD) factorial pattern with two treatment factors, namely the concentration of stevia sugar (A) with four types of treatment levels, A1 = 0% (100% sucrose); A2 = 1%; A3 = 2%; A4 = 3%. Concentration of CMC (B) with three types of treatment, B1 = CMC 0%; B2 = CMC 0.25%; B3 = CMC 0.5%. Each treatment was repeated twice to obtain Â 4 x 3 x 2 = 24 experimental units. The results show the brightest color produced by 100% sucrose with CMC 0% which is equal to 36.24 (L). The highest sugar content was produced in syrup with the addition of stevia 3% and CMC 0% which amounted to 34.46%. The highest viscosity is produced in syrup with the addition of 100% sucrose and CMC 0.5% which is equal to 365.2 cP.)